2011
DOI: 10.1002/adma.201101243
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Materials for High‐Performance MgB2 Wire

Abstract: Carbon‐encapsulated crystalline boron nanopowder and coarse magnesium powder are used as inexpensive tailored starting materials for the fabrication of high‐performance MgB2 superconducting wire. A low sintering temperature leads to a high critical current density, as a result of nanometer‐sized boron powder, surface oxidation preclusion by carbon encapsulation, and grain alignment by elongated magnesium coarse powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 28 publications
3
66
0
Order By: Relevance
“…Even at higher temperature (20 K), the critical current density in the malic acid-doped MgB 2 wire also exceeds 104 A cm −2 at 5 T. These critical current density values are the highest record published so far for an in situ processed wire. The measured critical temperature for the doped wire was estimated to be 34 K. It should be noted that the critical currents of the doped sample can be described by the percolation model (Kim et al 2011;Maeda et al 2013). All the fitting lines in Figure 1a were calculated from the percolation theory and are in good agreement with the measured data.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Even at higher temperature (20 K), the critical current density in the malic acid-doped MgB 2 wire also exceeds 104 A cm −2 at 5 T. These critical current density values are the highest record published so far for an in situ processed wire. The measured critical temperature for the doped wire was estimated to be 34 K. It should be noted that the critical currents of the doped sample can be described by the percolation model (Kim et al 2011;Maeda et al 2013). All the fitting lines in Figure 1a were calculated from the percolation theory and are in good agreement with the measured data.…”
supporting
confidence: 70%
“…Here, only four fitting parameters -the upper critical field (B c2 ), the anisotropy parameter (γ), the pinning force maximum (F m ), and the percolation threshold (P c ) -are needed to describe the field dependence of the critical current for each temperature. We previously reported that for polycrystalline wire samples, the percolation threshold, P c , is usually 0.26 (Shahabuddin et al 2014a;Kim et al 2011).…”
mentioning
confidence: 99%
“…Here we briefly discuss the origin of excellent low-field J c observed in the sintered ex-situ bulks. In addition to connectivity, flux pinning strength [9] and upper critical field [37] were reported to be essential factors that determine low-field J c of in-situ MgB 2 polycrystalline samples. Since microstructural analysis showed little sign of grain growth or refinement, we may assume that the predominant flux pinning, i.e.…”
Section: Microstructurementioning
confidence: 99%
“…MgB 2 attracted lots of attention because of its simple crystal structure, large coherence length, relatively high critical current density, and transparency of the grain boundaries. During the development for more than 10 years, MgB 2 has been fabricated [2][3][4][5][6][7][8][9][10]into bulks, single crystals, thin films, tapes and wires.…”
Section: Introductionmentioning
confidence: 99%